Express the equation cosecθ(3 cos 2θ+7)+11=0 in the form asin^2(θ) + bsin(θ) + c = 0, where a, b and c are constants.

We must first use the identity cosecθ = 1/sinθ. Now the equation becomes (1/sinθ)(3 cos 2θ+7)+11=0. Since we know that the question is asking for the answer in the form of asin2θ + bsinθ + c = 0, we realise that we must change cos 2θ into something containing sinθ instead. To do this we use the double angle formula cos2θ=1-2sin2θ. Substituting this into the equation we get (1/sinθ)(3 (1-2sin2θ)+7)+11=0. Simplifying this by multiplying out the brackets we find; (1/sinθ)(10-6sin2θ)+11=0. Multiplying out again gives us (10/sinθ)-6sinθ+11=0. Comparing this with the form of the answer that the question requires means we must multiply through by sinθ, giving us -6sin2θ + 11sinθ + 10 = 0.

Answered by George L. Maths tutor

5546 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve the simultaneous equation y+4x+1=0 and y^2+5x^2+2x+0.


How can I calculate the standard deviation of a data set?


express (3x + 5)/(x^2 + 2x - 15) - 2/(x - 3) as a single fraction its simplest form


Find the x-values of the turning points on the graph, y=(3-x)(x^2-2)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences